Basic concepts and recent advances in nanogels as carriers for medical applications - Iordana Neamtu; Alina Gabriela Rusu; Alina Diaconu; Loredana Elena Nita; Aurica P. Chiriac (Taylor & Francis Group, 2017)
Nanogels in biomedical field are promising and innovative materials as dispersions of hydrogel nanoparticles based on crosslinked polymeric networks that have been called as next generation drug delivery systems due to their relatively high drug encapsulation capacity, uniformity, tunable size, ease of preparation, minimal toxicity, stability in the presence of serum, and stimuli responsiveness. Nanogels show a great potential in chemotherapy, diagnosis, organ targeting and delivery of bioactive substances. The main subjects reviewed in this article concentrates on: (i) Nanogel assimilation in the nanomedicine domain; (ii) Features and advantages of nanogels, the main characteristics, such as: swelling capacity, stimuli sensitivity, the great surface area, functionalization, bioconjugation and encapsulation of bioactive substances, which are taken into account in designing the structures according to the application; some data on the advantages and limitations of the preparation techniques; (iii) Recent progress in nanogels as a carrier of genetic material, protein and vaccine. The majority of the scientific literature presents the multivalency potential of bioconjugated nanogels in various conditions. Today's research focuses over the overcoming of the restrictions imposed by cost, some medical requirements and technological issues, for nanogels' commercial scale production and their integration as a new platform in biomedicine.